Refinements of Kantorovich Inequality for Hermitian Matrices - Feixiang Chen (Journal of Applied Mathematics)
Some new Kantorovich-type inequalities for Hermitian matrix are proposed in this paper. We consider what happens to these inequalities when the positive definite matrix is allowed to be invertible and provides refinements of the classical results.